Pelaksanaan Program Ahlul Qur’an (PRO-AQ) Sebagai Sarana Percepatan Hafalan di Rumah Qur’an Al-Azhar Al-Syarif Kertak Hanyar Kalsel - Muhammad Iqbal Ansari; Iman Setya Budi (IAI Darussalam, 2020)
Based on Sofyan's research entitled Development of the Tahfiz Qur'an Movement in the Reformation Era in Indonesia, tahfizh Al-Qur'an learning is growing. It can be seen from the rapid development of Rumah Tahfizh which was triggered by Daarul Qur'an which was initiated by Yusuf Mansur which reached 300 more branches. The concept of Rumah Tahfizh was adopted by Al-Qur'an educational institutions in Indonesia, instead of the Al-Azhar Al-Syarif Qur'an House which was installed in Manarap Village, Banjar Regency, South Kalimantan Province. Based on the results of observations, learning at Al-Azhar Al-Syarif Qur'an House is carried out in 3 shifts, namely shift 1, shift 2, and the afternoon shift. Each shift was conducted 3 times in the discussion. Expect students to actively study in 1 week 3 times. The target of students to memorize each visit is 2 lines of the Al-Qur'an Standard Mushaf Madinah. But this target failed to be resolved due to several problems, in the approval of students not entering (permission or illness), strengthening memorization that had been deposited, still the process of developing reading improvements, or new students memorizing composting at the Qur'an House not at home. One of the alternatives to maximize the memorization of the Qur'an is the program held by Tahfidzh Quarantine 1 Day at Al-Azhar Al-Syarif Qur'an House. The purpose of quarantine tahfidzh 1 day is to accelerate memorization, and activities at school after quarantine is muroja'ah, which is repetition of memorization that has been completed by compiling quarantine programs, has improved memorization, learning will be efficient, both for improving memorization and reading.